(untitled) (Annual of the Faculty of Philosophy in Skopje, 2025)
This paper is focused on two main theoretical topics. First, it summarizes and critically analyzes the dominant contemporary interpretations of what is called “logical hylomorphism This expression, coined by John MacFarlane, designates the conception according to which the ontological distinction of form and matter, rooted in Aristotle’s philosophical writings, can be applied to arguments and inferences in order to show that the specifically logical element that they contain is related to their formal, and not to their material aspect. Second, in the light of the contemporary discussions on logical hylomprphism and its theoretical consequences, the author analyzes some of the dominant conceptions of informal logic as opposed to formal logic. The point of this analysis is to corroborate he main thesis of the paper: the idea that in order to avoid the current conceptual controversies concerning the status and the main preoccupations of logic as a discipline, it is necessary to reconceptualize some of its fundamental notions and theoretical distinctions, in the light of an enlarged conception of rationality, which includes not only the anaytical, but also the dialectical aspects of reasoning and argumentation.